RNase T2 restricts TLR13-mediated autoinflammation in vivo - Gomez-Diaz, Carlos; Greulich, Wilhelm; Wefers, Benedikt; Wang, Meiyue; Bolsega, Silvia; Effern, Maike; Varga, Daniel P; Han, Zhe; Chen, Minyi; Bérouti, Marleen; Leonardi, Natascia; Schillinger, Ulrike; et al. (The Journal of experimental medicine, 2025)
RNA-sensing TLRs are strategically positioned in the endolysosome to detect incoming nonself RNA. RNase T2 plays a critical role in processing long, structured RNA into short oligoribonucleotides that engage TLR7 or TLR8. In addition to its positive regulatory role, RNase T2 also restricts RNA recognition through unknown mechanisms, as patients deficient in RNase T2 suffer from neuroinflammation. Consistent with this, mice lacking RNase T2 exhibit interferon-dependent neuroinflammation, impaired hematopoiesis, and splenomegaly. However, the mechanism by which RNase T2 deficiency unleashes inflammation in vivo remains unknown. Here, we report that the inflammatory phenotype found in Rnaset2-/- mice is completely reversed in the absence of TLR13, suggesting aberrant accumulation of an RNA ligand for this receptor. Interestingly, this TLR13-driven inflammatory phenotype is also fully present in germ-free mice, suggesting a role for RNase T2 in limiting erroneous TLR13 activation by an as yet unidentified endogenous ligand. These results establish TLR13 as a potential self-sensor that is kept in check by RNase T2.